Development of strategic resilience framework for small businesses post-COVID-19 - Zahra Gorjian Khanzad; Ali A. Gooyabadi (Businesses, 2021)
The detrimental transboundary effect of COVID-19 exhibits an unprecedented circumstance for organizational resilience. This proposed research paper aims to analyze the impact of COVID-19 on small businesses (SBs) worldwide towards developing a strategic resilience framework. This framework enables the development of resilient strategies that SBs can utilize to survive and sustain their livelihood post-COVID-19. It is profoundly challenging to cope with the consequences of a devastating global pandemic with enormous negative economic side-effects and survive given reduced income, jobs lost, etc. This paper utilizes different models, such as Meyer's Model, the PESTEL model, and the Comprehensive Organizational Model, to discuss the process of adaptations to market shocks. This adaptation methodology consists of different anticipatory, responsive, and rehabilitation phases, leading to organizational resilience. A conceptual framework is proposed through a qualitative analysis of existing academic literature concerning strategic resilience for small businesses facing environmental jolts such as COVID-19. By developing the proposed strategic resilience framework, other methods and theories, including the adaptability of small- and medium-sized organizations, will be addressed.
Keywords: 650; organizational resilience; corporate culture; small businesses; COVID-19